A Case Study Demonstrating the Use of Appreciative Inquiry in a Financial Coaching Program. (December 2016) - Delgadillo, Lucy M.; Palmer, Lance; Goetz, Joseph
Abstract : This article presents a case study of appreciative inquiry applied to client work within the context of a solution‐focused, financial coaching program. Appreciative inquiry (AI) is a process—a generative process—wherein a client envisions, describes, and constructs a new meaning or reality through structured questions and answers, and then designs a way to get there (to their destiny). The origins, tenets, and applications of AI approach are described, followed by a case study to facilitate a client's overcoming of a specific, maladaptive money script utilizing AI. The article provides implications for financial practitioners and a foundation for future research on the effectiveness of the AI approach in financial coaching.